Literature Review: Relationship Between Rubber Factory Pollution Exposure and Reactive Oxygen Species (ROS) Levels in Workers - Pasaribu, Sumihar MR; Purba, Amril; Perangin-angin, Guntur; Siahaan, Jekson Martiar (Buletin Farmatera, 2025)
Abstract: Working in rubber factories exposes personnel to a cocktail of airborne contaminants—hydrogen sulfide, organic solvents, and fine dust—that jeopardise health over the long term. A key pathological response to such pollution is the upsurge in reactive oxygen species (ROS), which drives oxidative stress and underlies injury to cells, tissues, and organ systems. The present review compiles biomarker and mechanistic data showing how encounters with factory fumes correlate with elevated ROS levels in exposed workers. Cross-sectional surveys and laboratory experiments consistently report raised indicators such as malondialdehyde (MDA) and 8-hydroxy-2-deoxyguanosine (8-OHdG), establishing a robust link between airborne toxins and molecular damage. Genetic variants that weaken antioxidant enzymes further shape individual risk, reminding us that not every worker faces the same burden even under identical exposure conditions. Consequences typically affect the respiratory tract, heart, and metabolic pathways, reinforcing calls for stronger engineering controls, personal monitoring, and health surveillance in the plant. Early trials of antioxidant supplements show promise for damping ROS pathways, yet the field still lacks evidence-based protocols that tailor interventions to sources and dosages of pollution. By clarifying these oxidative processes, the review aims to guide regulators and industry managers in crafting rules that truly protect workers' lives and livelihoods